A influência do alinhamento estratégico da tecnologia de informação no desempenho empresarial: um estudo sobre o impacto da orientação estratégica na integração, uso e benefícios desta tecnologia ao negócio - Yoshikuni, Adilson Carlos (2015)
This study aims to evaluate the influence of Information Technology (IT) in the Firm Performance under orientation of Business Strategy. The research is a specific cut of the IT strategic alignment of technology integration, use and value of IT to the business and influences several of the firm's performances perspectives. The business strategy gets cut in the study of strategic orientation to impact the IT integration to strategy and business processes. The research used the technique of structural equations modeling with the PLS-PM an empirical study of 222 companies. The results show the influence of IT on business performance, in explaining the variability of 34.1 % of learning & growth performance, 46.1 % of the internal process performance, 44.7 % of market performance, and 32.7 % of the performance financial. The results show the influence of IT on firm performance and the impact of the strategy on integration, use and value of IT to strategy and business processes. The study explains 74.1% of the variability of the use and strategy value of IT and business processes, and the various effects of IT on firm performance. In addition, the study demonstrated the importance and emphasis given by the companies in the strategy orientation aspects. The model made IT possible to explain the variability of various performance perspectives, and suggests other ways to measure the adoption and IT use in the organizations.